Successful Aortic Valve Repair in Pediatric Patients Using the Trussler Technique: A Five-Year Case Series at Soetomo Hospital Surabaya - Bagus Rifnaputra, Mochamad; Soebroto, Heroe; Rakhman Hakim, Arief; Akbar, Erdyanto; Daswin Pagehgiri, Hari (Journal of Neonatal Surgery, 2025)
Background: The coexistence of ventricular septal defect (VSD) and aortic regurgitation (AR) presents complex challenges in pediatric cardiac care. Undetected and untreated cases can lead to severe morbidity and mortality, emphasizing the importance of effective surgical intervention. While the Trussler technique has shown promise in addressing aortic valve pathologies, its application in the Indonesian population remains understudied. Discussion: We present a retrospective case series of eight pediatric patients with VSD and AR undergoing aortic valve repair using the Trussler technique at Soetomo General Academic Hospital. Preoperatively, patients exhibited varying degrees of AR severity. Postoperatively, significant improvements were evident, with 87.5% achieving complete closure of VSD without residual flow, and 87.5% demonstrating only Mild AR. These outcomes highlight the efficacy of the Trussler technique in managing complex cardiac anomalies, particularly in cases of VSD, which are associated with higher rates of AR. Conclusion: Our findings support the efficacy of aortic valve repair in pediatric patients with concurrent VSD and AR, emphasizing the importance of tailored surgical approaches. Further research with larger cohorts and longer follow-up periods is needed to validate these outcomes and refine clinical management strategies..